SIMULATION OF TUITION FEES IN COMPETITIVENESS MANAGEMENT OF HIGHER EDUCATION INSTITUTIONS (CASE OF UKRAINE’S UNIVERSITIES) - Panchyshyn, Stephen; Hrynkevych, Olha; Marets, Oksana; Demchyshak, Nazariy; Popadynets, Nazariy (Scientific Journal of Pedagogy and Economics, 2020)
The purpose of study is to simulate the tuition fees in Ukrainian higher education institutions (HEIs), taking into account the internal and external factors of their activity. The choice of variable models is based on the theoretical study and classification of pricing factors in higher education. The empirical part of the research is performed according to online data of 35 Ukrainian universities. Using correlation analysis, we found that the main factors that impact variability the tuition fees variation are: 1) academic reputation of HEI, 2) popularity of the study program among entrants, 3) population income in the region of HEIs activity. To simulate the tuition fees, taking into account the essential factors, the programming language R was used. The modeling found that there is an issue with the overpricing and underpricing of education in Ukrainian HEIs in comparison with its theoretically justifiable value. Competition in the market of educational services forces Ukrainian universities to pursue a pricing policy that is accompanied by both too high and low tuition fees, which do not cover training costs and do not provide long-term development. The results of modeling could be used to improve the quality of decision making process in HEIs management.